RICE VALUE CHAIN : A STRUCTURATION THEORY APPROACH - Maria Widyarini; Gandhi Pawitan (Research Report - Humanities and Social Science, 2011)
The value chains of rice has created a significant impact in the domestic rice price as well as in Indonesia. As we know from many literatures that providing rice product in time and at different places in the market is very important, especially in Indonesia. The facts that import rice is cheaper than domestic rice price has give a negative impact to the farmers. Thus, the performance of a value chains of rice is related to its structure and strategies of the actors operating these chains or channels are important to be considered by government. Value chain analysis is the sequence analysis of related business activities (functions) from specific inputs for a particular product to primary production, transformation, marketing and up to final consumption. In other words, we can say that value chains is perfoming several functions i.e start from producer (rice producer or farmers), processors (farmer or trader), traders (retailer or wholesaler) and transporter (transportation and storage are important functions in the rice channel distributuion system). Reffering to the description of the rice market in Indonesia, we would like to emphasize that there is some room for value chains based on informal collaboration concering exchange information and financial arrangement between farmers and rice traders and rice traders to others. This study analyse construct from three different theory and models namely value chains, structuration theory and institutional economics related with rice condition in Indonesia. The result of this study are nine proposition that will be tested for futher research. Further, it will be applied for analyzing in more detail all types of agents/actors that perform different chains functions in the rice domestic market in Indonesia.Key words : Indonesian rice, rice value chains, structuration theory, institutional economics